1996
DOI: 10.1007/bf01292626
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin (5-HT) release in the dorsal raph� and ventral hippocampus: Raph� control of somatodendritic and terminal 5-HT release

Abstract: Somatodendritic and terminal release of serotonin (5-HT) was investigated by simultaneously measuring extracellular concentrations of 5-HT, 5-hydroxyindole-3-acetic acid (5-HIAA) and homovanillic acid (HVA) in the dorsal raphé and ventral hippocampus in freely moving rats. Perfusion of tetrodotoxin (TTX, 1 microM and 10 microM) into the dorsal raphé simultaneously decreased dorsal raphé and hippocampal 5-HT release. However, following TTX perfusion into the hippocampus (10 microM), hippocampal 5-HT release was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 34 publications
5
29
1
1
Order By: Relevance
“…These may release NA in an impulse-dependent manner, as observed in the forebrain (L 'Heureux et al, 1986). Likewise, most previous reports support the notion that the 5-HT release in the DR varies in parallel with serotonergic activity Artigas, 1996, Casanovas et al, 1997;Matos et al, 1996;Celada et al, 2001). As previously reported in the hippocampus of awake rats (Done and Sharp, 1994), 8-OH-DPAT increased NA release in the DR.…”
Section: Methodological Aspectssupporting
confidence: 69%
“…These may release NA in an impulse-dependent manner, as observed in the forebrain (L 'Heureux et al, 1986). Likewise, most previous reports support the notion that the 5-HT release in the DR varies in parallel with serotonergic activity Artigas, 1996, Casanovas et al, 1997;Matos et al, 1996;Celada et al, 2001). As previously reported in the hippocampus of awake rats (Done and Sharp, 1994), 8-OH-DPAT increased NA release in the DR.…”
Section: Methodological Aspectssupporting
confidence: 69%
“…Also, the application of R(ϩ)baclofen in the DRN reduced the striatal 5-HT output. These changes may be attributed to the inhibition of firing activity of serotonergic neurons by GABA A and GABA B receptor activation (Gallager and Aghajanian, 1976;Innis and Aghajanian, 1987) since the 5-HT release in the DRN and forebrain is sensitive to the propagation of nerve impulses (Carboni and Di Chiara, 1989;Sharp et al, 1990;Matos et al, 1996). The remarkable decrease of the 5-HT release in striatum after the application of 1 µM GABA in the DRN suggests a very high sensitivity of serotonergic neurons to the action of this neurotransmitter.…”
Section: Dual Action Of Baclofen On Serotonergic Neuronsmentioning
confidence: 90%
“…Also, the activation of 5-HT 1A receptors, coupled to the same effector system as GABA B receptors (Innis et al, 1988;Williams et al, 1988), results in a reduction of the 5-HT output in the DRN (Matos et al, 1996;Casanovas et al, 1997). This discrepancy could be due to a preferential action of baclofen on GABA B receptors located on inhibitory GABAergic inputs to serotonergic neurons (Wang et al, 1992, Jolas andAghajanian, 1997).…”
Section: Dual Action Of Baclofen On Serotonergic Neuronsmentioning
confidence: 94%
“…However, recent studies have shown that dendritic dopamine and serotonin release are also fully TTX-and calcium-dependent (Matos et al, 1996;Santiago and Westerink, 1992).…”
Section: Ttx-dependencymentioning
confidence: 99%